2012
DOI: 10.1159/000339254
|View full text |Cite
|
Sign up to set email alerts
|

Intrafascial Dissection Significantly Increases Positive Surgical Margin and Biochemical Recurrence Rates after Robotic-Assisted Radical Prostatectomy

Abstract: Introduction: Improved visualization and magnification in robot-assisted laparoscopic radical prostatectomy (RALRP) has tempted many urologists to dissect the neurovascular bundle closer to the prostate following the layers of the pseudo-capsule of the prostate. This might bear a higher risk of decreased tumor control. Materials and Methods: An analysis of a consecutive series of 186 patients who underwent RALRP at our institution was performed. The outcome of patients with intrafascial nerve-sparing (INS) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…PSM rates of intrafascial group stratified by pathological tumor stages could be found in Additional files 2 and 3, which showed that the pooled PSM rate was 9.7% (236/2423, 95% CI: 7.0–12.4%) in pT2 cancers (Additional file 2: Figure S1) and 44.0% (208/527, 95% CI: 34.9–53.2%) in pT3 cancer (Additional file 3: Figure S2). Overlapping higher rates could be seen in terms of the PSM rate in pT2 cancer that the studies of Curto (2006) [11] and Mortezavi (2012) [16], which also reported a significantly higher PSM rate than the pooled rate; however, this overlap was not observed with regard to the PSM rate in pT3 cancer.
Fig. 2Forest plot for one-arm meta-analysis of studies adopting the intrafascial technique in terms of total PSM rate in all-stage disease stratified by surgical types.
…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…PSM rates of intrafascial group stratified by pathological tumor stages could be found in Additional files 2 and 3, which showed that the pooled PSM rate was 9.7% (236/2423, 95% CI: 7.0–12.4%) in pT2 cancers (Additional file 2: Figure S1) and 44.0% (208/527, 95% CI: 34.9–53.2%) in pT3 cancer (Additional file 3: Figure S2). Overlapping higher rates could be seen in terms of the PSM rate in pT2 cancer that the studies of Curto (2006) [11] and Mortezavi (2012) [16], which also reported a significantly higher PSM rate than the pooled rate; however, this overlap was not observed with regard to the PSM rate in pT3 cancer.
Fig. 2Forest plot for one-arm meta-analysis of studies adopting the intrafascial technique in terms of total PSM rate in all-stage disease stratified by surgical types.
…”
Section: Resultsmentioning
confidence: 95%
“…It was possible to calculate the heterogeneity among the included studies as I 2 was 86.38%. Three studies showed significantly higher PSM rates than the pooled rate, which included the studies of Curto 2006 [11], Choi 2012 [18], and Mortezavi 2012 [16], with a PSM rate of 30.8% (127/413, 95% CI: 26.3–35.2%), 34% (17/50, 95% CI: 20.9–47.1%), and 35% (28/80, 95% CI: 24.5–45.5%), respectively, whereas the VIP team reported a notably lower PSM rate of 1/46 [27]. No obvious differences could be detected among the 3 surgery types of LRP, RRP, and RALRP.…”
Section: Resultsmentioning
confidence: 99%
“…This in turn results in maximizing the improvement of postoperative continence and potency rate without compromising the oncological efficacy 25 28 . Controversially, the IFRP nerve sparing technique might result in the increased rate of PSM and high biochemical recurrence risk 20 , 29 . This is the first systematic review and meta-analysis of all the currently available evidences regarding IFRP comparison with NIFRP.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies demonstrated a higher rate of pT2 stage in IFRP group, but a higher rate of pT3 stage in NIFRP group. The reason for this could be attributed to an earlier preoperative clinical stage, lower PSA level and Gleason score selected for the IFRP patients in some studies 18 , 20 , 22 . Our meta-analysis study demonstrated a significantly higher BFS rate in IFRP group than NIFRP group at pT3 stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation